2016
DOI: 10.1186/s13006-016-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prelacteal feeding in the rural population of northwest Ethiopia: a community cross-sectional study

Abstract: BackgroundPrelacteal feeding has continued as a deep-rooted nutritional malpractice in developing countries. Prelacteal feeding is a barrier for implementation of optimal breastfeeding practices, and increases the risk of neonatal illness and mortality. However, its determinants are not well studied, which are essential to design intervention. This study aimed to assess the prevalence and determinants of prelacteal feeding among mothers with children aged 6–24 months in the rural population of northwest Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
53
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 34 publications
15
53
5
1
Order By: Relevance
“…Pre-lacteal feeding also has many implications for exclusive breastfeeding and resulting consequences since by definition, these children are not exclusively breastfed. Similar to our study findings in which mothers reportedly used pre-lacteals to clean the throats of the newborns, a study that assessed the factors associated with pre-lacteal feeding in the rural population of northwest Ethiopia reported that the practice was largely associated with poor knowledge of IYCF [33]. When children are given complementary foods from the age of 6 months, the foods should be adequate to support growth (i.e., an adequate quantity of food for each meal and number of meals per day) and have the right consistency, nutrients and energy density.…”
Section: Discussionsupporting
confidence: 76%
“…Pre-lacteal feeding also has many implications for exclusive breastfeeding and resulting consequences since by definition, these children are not exclusively breastfed. Similar to our study findings in which mothers reportedly used pre-lacteals to clean the throats of the newborns, a study that assessed the factors associated with pre-lacteal feeding in the rural population of northwest Ethiopia reported that the practice was largely associated with poor knowledge of IYCF [33]. When children are given complementary foods from the age of 6 months, the foods should be adequate to support growth (i.e., an adequate quantity of food for each meal and number of meals per day) and have the right consistency, nutrients and energy density.…”
Section: Discussionsupporting
confidence: 76%
“…7,[9][10][11][12][13] It is also lower than the results found in different parts of Ethiopia. 5,6,14 However, it is slightly higher than the result of a study done in Nigeria. 15 The difference might stem from the sociodemographic differences among the study participants and methodological differences among the studies.…”
Section: Discussioncontrasting
confidence: 53%
“…[8][9][10] In the current study 31.2% of the study participants received prelacteal feeding in the first three days of life which was higher compared to the studies of Dandekar et al (28%), Tarikul et al (26.8%). 11,12 Among 247 study participants, exclusive breastfeeding for six months was received by 10.2% of infants which was alike compared to other studies conducted by Sahithyaa J et al [13][14][15][16] Maternal perception that only breastfeeding is not sufficient to fulfill the need and growth of infant were found to be strong factor in early cessation of exclusive breastfeeding. Maternal factors like inadequate secretion of breastmilk, maternal illness and household responsibilities were found to influence exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 79%